The Representation of Universal Moralvalue “Freedom” in Linguistic Consciousness of Russian Culture Bearers - Zhamaletdinova, E.K. (Vestnik Rossijskogo universiteta družby narodov. Seriâ: Teoriâ âzyka, semiotika, semantika (Online), 2017)
This paper examines the meaning of universal moral value “freedom” reflected in linguistic consciousness of Russian culture-bearers. It contains the results of the analysis of the way the value is represented on official and common levels of consciousness. Within the framework of the research on the official level of consciousness the data of encyclopedic dictionaries is analysed. That aims to reflect the scientific worldview of Russian culture-bearers. Their everyday worldview is revealed through the analysis of the data of lexicographical literature, Russian text corpus, paroemiological fund as well as the results of associative and psycho-semantic experiments. The methodology of the research is based on the theory of activity approach elaborated by Moscow psycholinguistic School and the triangulation approach designed by V.A. Yanchuk. The latter approach allows to integrate knowledge of different layers and the methodology aiming at obtaining the most precise findings. The results of the given research shows the variety of meanings of the value “freedom” used on the common level of consciousness. That indicates the practical attitude to the value considered in the perception of the Russians. The methods of the analysis has a great potential for further research of different notions.